2014
DOI: 10.1126/science.1246249
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Long-Range Charge Separation in Organic Semiconductor Photovoltaic Diodes

Abstract: Understanding the charge-separation mechanism in organic photovoltaic cells (OPVs) could facilitate optimization of their overall efficiency. Here we report the time dependence of the separation of photogenerated electron hole pairs across the donor-acceptor heterojunction in OPV model systems. By tracking the modulation of the optical absorption due to the electric field generated between the charges, we measure ~200 millielectron volts of electrostatic energy arising from electron-hole separation within 40 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

86
1,093
7
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 880 publications
(1,189 citation statements)
references
References 44 publications
86
1,093
7
3
Order By: Relevance
“…Recent spectroscopic measurements on organic photovoltaic systems have reported that charged photo excitations can be generated on r100-fs time scales [2][3][4][5][6][7][8][9][10] ; however, full charge separation to produce photocarriers is expected to be energetically expensive given strong Coulombic barriers due to the low dielectric constant in molecular semiconductors. Nonetheless, experiments by Gélinas et al 11 in which Starkeffect signatures in transient absorption spectra were analysed to probe the local electric field as charge separation proceeds, indicate that electrons and holes separate by B40 Å over the first 100 fs and evolve further on picosecond time scales to produce unbound charge pairs. Concurrently, Provencher et al (FP, manuscript in preparation) have demonstrated, via transient resonance Raman measurements, clear polaronic vibrational signatures on sub-100 fs on the polymer backbone, with very limited molecular reorganization or vibrational relaxation following the ultrafast step.…”
mentioning
confidence: 99%
“…Recent spectroscopic measurements on organic photovoltaic systems have reported that charged photo excitations can be generated on r100-fs time scales [2][3][4][5][6][7][8][9][10] ; however, full charge separation to produce photocarriers is expected to be energetically expensive given strong Coulombic barriers due to the low dielectric constant in molecular semiconductors. Nonetheless, experiments by Gélinas et al 11 in which Starkeffect signatures in transient absorption spectra were analysed to probe the local electric field as charge separation proceeds, indicate that electrons and holes separate by B40 Å over the first 100 fs and evolve further on picosecond time scales to produce unbound charge pairs. Concurrently, Provencher et al (FP, manuscript in preparation) have demonstrated, via transient resonance Raman measurements, clear polaronic vibrational signatures on sub-100 fs on the polymer backbone, with very limited molecular reorganization or vibrational relaxation following the ultrafast step.…”
mentioning
confidence: 99%
“…A tomography protocol has been discussed in the context of energy transfer in condensed phase by non-linear spectroscopy [77,78]. Detection of experimental signals such as the electric field generated by the charge separation at heterojunction could also give information about non-monotonous evolution [79].…”
Section: Resultsmentioning
confidence: 99%
“…This is a critical distinction as several observations of excited state coherences have been made. 28,[53][54][55][56] Moreover, measurements that invoke charge carrier coherence [27][28][29] are predicated on the existence of excited state coherence.…”
Section: Discussionmentioning
confidence: 99%